Effects of Post-translational Modifications on Membrane Localization and Signaling of Prostanoid GPCR–G Protein Complexes and the Role of Hypoxia - Sikarwar, Anurag S.; Bhagirath, Anjali Y.; Dakshinamurti, Shyamala (The Journal of membrane biology, 2019)
G protein-coupled receptors (GPCRs) play a pivotal role in the adaptive responses to cellular stresses such as hypoxia. In addition to influencing cellular gene expression profiles, hypoxic microenvironments can perturb membrane protein localization, altering GPCR effector scaffolding and altering downstream signaling. Studies using proteomics approaches have revealed significant regulation of GPCR and G proteins by their state of post-translational modification. The aim of this review is to examine the effects of post-translational modifications on membrane localization and signaling of GPCR–G protein complexes, with an emphasis on vascular prostanoid receptors, and to highlight what is known about the effect of cellular hypoxia on these mechanisms. Understanding post-translational modifications of protein targets will help to define GPCR targets in treatment of disease, and to inform research into mechanisms of hypoxic cellular responses. Graphic Abstract